Reliability of measurements of tongue and hand strength and endurance using the Iowa Oral Performance Instrument with elderly adults. (March 2015) - Adams, Valerie; Mathisen, Bernice; Baines, Surinder; Lazarus, Cathy; Callister, Robin
Abstract Purpose: This study investigated the reliability of tongue and hand strength and endurance measurements in old adults using the Iowa Oral Performance Instrument (IOPI). Method: Thirty aged-care residents (6 males and 24 females) aged 79–97 years were tested on four occasions two weeks apart to determine test–retest reliability. The primary outcome measures were isometric anterior and posterior tongue and hand strength (best of three trials) and isometric tongue and hand endurance time at 50% of maximal strength. Results: Changes in the mean between sessions for tongue and hand strength indicated acceptable (< 10%) reliability particularly with familiarisation. The within-subject variation (mean-typical error expressed as a coefficient of variation, CV) indicated higher than acceptable variation for anterior and posterior tongue and hand strength. Intra-class correlations (ICC) indicated moderate to strong reliability for anterior (ICC 0.58–0.77) and posterior (ICC 0.77–0.84) tongue strength and hand strength (ICC 0.79–0.96). No tongue or hand endurance measures were regarded as reliable. Conclusion: These findings indicate that overall tongue and hand strength values demonstrate acceptable reliability in the elderly, especially where familiarisation with the IOPI is provided. Further investigation to reduce sources of variability in tongue endurance measurements is warranted. Implications for Rehabilitation Examination of tongue strength is a frequent component of the clinical assessment of swallowing by speech-language pathologists. Frailty is a term used to describe the condition of people who have lost functional abilities and are likely to deteriorate further, and is common in older age. Tools that can reliably measure muscle strength in an elderly population are valuable. The IOPI is reliable for the measurement of tongue and hand strength in an elderly population.